Beyond Unit 731: Japanese Medical Atrocities in the Greater Pacific War, 1931-45 — Context and Implications - Eagan, Sheena M.; Durant, David M. (My University, 2025)
Much is known about the horrific medical experiments conducted by Nazi physicians and researchers at Auschwitz and other concentration camps. Less well known are the numerous horrific atrocities performed by Japanese medical personnel during the Second World War. Unit 731, a biological warfare research complex, performed hideous medical experiments that claimed thousands of lives. Its work culminated in a number of biological warfare attacks as part of Japan’s war in China. Unfortunately, such horrific acts went well beyond Unit 731, involving both the Japanese Army and Navy Medical Corps, and the civilian Japanese medical establishment. This included regular involvement of medical personnel in war crimes, killing of non-ambulatory wounded, and the widespread practice of vivisection as a tool of both medical research and education. This presentation will explore the history of these crimes, their context, and the broader conditions that made them possible.
Keywords: Unit 731, biological warfare, Japan, Manchuria, Shiro Ishii, medical experimentation, medical ethics, medical crimes, military medicine, military medical ethics, World War II, Pacific War